1989
DOI: 10.1128/jb.171.6.3583-3585.1989
|View full text |Cite
|
Sign up to set email alerts
|

Intergeneric conjugation between Escherichia coli and Streptomyces species

Abstract: We have constructed Escherichia coli-Streptomyces shuttle plasmids which are capable of conjugal transfer from E. coli to Streptomyces spp. These plasmids contained the pBR322 and pUJlOl origins of replication and the RK2 (IncP) origin of transfer. The transfer of plasmid was specifically dependent the presence of a 760-base-pair, cis-acting, oriT-containing fragment and on RP4 (IncP) functions supplied in trans. Conditions of mating and selection of exconjugants were analyzed with Streptomyces lividans as rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
175
1
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(180 citation statements)
references
References 14 publications
0
175
1
4
Order By: Relevance
“…Escherichia coli strains used in plasmid transformations or for phage propagation were grown as described by Sambrook et al (1989). The DNA-methylation-deficient E. coli strain ET12567(pUZ8002) used in conjugal transfer of plasmids from E. coli to S. venezuelae was grown on LB agar supplemented as required with ampicillin (Ap; 50 mg ml 21 ), Cm (25 mg ml 21 ), Am (50 mg ml 21 ), Ts (25 mg ml 21 ) and kanamycin (Km, 50 mg ml 21 ) for specific selections (Mazodier et al, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…Escherichia coli strains used in plasmid transformations or for phage propagation were grown as described by Sambrook et al (1989). The DNA-methylation-deficient E. coli strain ET12567(pUZ8002) used in conjugal transfer of plasmids from E. coli to S. venezuelae was grown on LB agar supplemented as required with ampicillin (Ap; 50 mg ml 21 ), Cm (25 mg ml 21 ), Am (50 mg ml 21 ), Ts (25 mg ml 21 ) and kanamycin (Km, 50 mg ml 21 ) for specific selections (Mazodier et al, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…The resultant plasmid (pLST9734) was initially propagated in E. coli NM522, before being introduced into E. coli S17-1, the donor strain used for conjugal transfer to Streptomyces spp. (modified from Bierman et al, 1992;Mazodier et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The recombinant DNA may be introduced into K. setae by an E. coli/ Streptomyces conjugation using an IncP-plasmid (RK2) origin transfer. 34,35 However, we found that the transformation of K. setae KM-6054 was improved by electroporation (approximately 10-to 100-fold higher than the conjugation with E. coli and IncP-plasmid). K. setae generated submerged spores in the liquid culture and DNA was introduced into the submerged spores by electroporation.…”
Section: Characterization Of Bafilomycin Biosynthesismentioning
confidence: 83%